2023
DOI: 10.1002/ajmg.b.32959
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gut microbiota on the development of most prevalent neurodegenerative dementias and the potential effect of probiotics in elderly: A scoping review

David Mateo,
Montse Marquès,
José L. Domingo
et al.

Abstract: Dementia is one of today's greatest public health challenges. Its high socio‐economic impact and difficulties in diagnosis and treatment are of increasing concern to an aging world population. In recent years, the study of the relationship between gut microbiota and different neurocognitive disorders has gained a considerable interest. Several studies have reported associations between gut microbiota dysbiosis and some types of dementia. Probiotics have been suggested to restore dysbiosis and to improve neuroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Depletion of Prevotellaceae has been associated with increased production of pro-inflammatory cytokines TNF-α and IL-1β in serum and decreased butyrate production in the gut, which has been shown to provide a neuroprotective effect by restoring the blood-brain barrier (BBB) following TBI. 93,94 Additionally, the Prevotella genus has been demonstrated to increase the concentration of short-chain fatty acids (SCFAs) in pigs; SFCAs inhibit inflammation and are potentially protective against dementia risk 95,96 . Yet, certain species of Prevotella (a genus within Prevotellaceae) have been shown to decrease SCFA production and perpetuate intestinal inflammation 97 .…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of Prevotellaceae has been associated with increased production of pro-inflammatory cytokines TNF-α and IL-1β in serum and decreased butyrate production in the gut, which has been shown to provide a neuroprotective effect by restoring the blood-brain barrier (BBB) following TBI. 93,94 Additionally, the Prevotella genus has been demonstrated to increase the concentration of short-chain fatty acids (SCFAs) in pigs; SFCAs inhibit inflammation and are potentially protective against dementia risk 95,96 . Yet, certain species of Prevotella (a genus within Prevotellaceae) have been shown to decrease SCFA production and perpetuate intestinal inflammation 97 .…”
Section: Discussionmentioning
confidence: 99%
“…In early Parkinson's disease (PD), the microbial community of the gut is altered before motor symptoms fully manifest [4][5][6] , and may play a role in disease susceptibility 7,8 . At autopsy, -synuclein-containing Lewy bodies, which are the pathological hallmark of PD 5 , are found at all levels throughout the gut-brain axis, including the central, autonomic, and enteric neurons 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The gut may then become a source of seeding -synuclein 12 which is tra cked to the brain. The microbiome also appears to be important in the later stages of PD, as microbial shifts delay the absorption of dopaminergic drugs 13 and correlate with more severe clinical symptoms including PD dementia 4,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Of these, Lactiplantibacillus (Lactobacillus) plantarum appears to have the most promising results in the intervention of symptoms associated with neurodegeneration [ 78 , 79 , 80 ]. Several authors have suggested that the use of Lactiplantibacillus plantarum , alone or in combination, improves specific symptoms such as motor, cognitive and psychiatric signs in neurodegenerative processes [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Research regarding these effects has increased in the last decades, making it necessary to compare with the results obtained.…”
Section: Introductionmentioning
confidence: 99%